PENGEMBANGAN DOSEN DI LINGKUNGAN SEKOLAH TINGGI ILMU SOSIAL DAN ILMU POLITIK AMAL ILMIAH YAPIS WAMENA KABUPATEN JAYAWIJAYA - Aini, Nur (JI@P, 2017)
Implementation of development policies carried out by the faculty College of Social Sciences and Political Science Jayawijaya. Implementation of development policies carried out by the faculty College of Social Sciences and Political Science Jayawijaya Wamena is a strategic step in order to achieve quality lecturers. The purpose of this study was to analyze: how policy implementation lecturer in education programs formal and non-formal education, identify and analyze the factors supporting and inhibiting factors in the development of lecturers, and efforts to improve the effectiveness of the implementation of development policy lecturer at STISIP-AI Yapis Wamena. This research is a qualitative descriptive approach. The results showed that there was a lack of clarity contents of the policy, the budget provided inadequate, dispositions related to cognition and organizational structures associated with coordination. Efforts to improve the effectiveness of policy implementation by providing opportunities for faculty to continue their education in order to achieve academic qualifications. Advice given on this research, lecturers development program in the STISIP A-I Yapis Wamena should be improved. Keywords : Implementation, Policy, Development Lecturer